2017
DOI: 10.1161/circep.117.005485
|View full text |Cite
|
Sign up to set email alerts
|

Association Between QT-Interval Components and Sudden Cardiac Death

Abstract: Background Several reports have demonstrated that prolongation of the QT interval is associated with sudden cardiac death (SCD). However, it is unknown whether any of the components within the QT interval are responsible for its association with SCD. Methods and Results We examined the association of the individual QT interval components (R-wave onset to R-peak, R-peak to R-wave end, ST-segment, T-wave onset to T-peak, and T-peak to T-wave end) with SCD in 12,241 participants (54 ± 5.7 years; 26% black; 55% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 24 publications
2
55
0
3
Order By: Relevance
“…to T-peak is associated with increased SCD risk and incident atrial fibrillation in community-based cohorts without prevalent cardiovascular disease (O'Neal et al, 2017;Roberts et al, 2017). We find here a distinctive positive association between HIV infection and both T-wave components.…”
Section: Discussionsupporting
confidence: 48%
See 3 more Smart Citations
“…to T-peak is associated with increased SCD risk and incident atrial fibrillation in community-based cohorts without prevalent cardiovascular disease (O'Neal et al, 2017;Roberts et al, 2017). We find here a distinctive positive association between HIV infection and both T-wave components.…”
Section: Discussionsupporting
confidence: 48%
“…Prior studies have reported the association between longer T‐peak to T‐end and increased risk for SCD in cohorts with pre‐existing heart disease (Goldenberg & Moss, ; Morin et al, ; Panikkath et al, ; Rosenthal et al, ; Shimizu et al, ; Yamaguchi et al, ). In contrast, prolonged T‐onset to T‐peak is associated with increased SCD risk and incident atrial fibrillation in community‐based cohorts without prevalent cardiovascular disease (O'Neal et al, ; Roberts et al, ). We find here a distinctive positive association between HIV infection and both T‐wave components.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify cases of SCD in ARIC, cases of cardiovascular death that occurred by December 31, 2012, were reviewed and adjudicated by a committee of electrophysiologists, general cardiologists, and internists, as previously described. [13]…”
Section: Methodsmentioning
confidence: 99%